Analysis of Indigenous Teachers’ Theses: Autobiographical Narratives of Inequality - Solís-Calvo, Ana Magdalena (2026)
Introduction. The structural and historical inequality affecting Indigenous teaching staff in Mexico –since the creation of the educational system, the rationality of schooling, and the imposition of a national language that disregards Indigenous cultures– continues to be present in their educational narratives. Methods. Situated within a sociocultural and discourse analysis perspective, this study draws on Black and Latin American feminist theory to conduct an intersectional analysis of six undergraduate theses. Its aim is to understand the inequality embedded in autobiographical narratives regarding the race/gender/class system throughout the life trajectories of Indigenous teachers. Results. The findings reveal the inequalities faced by Indigenous teachers across their educational and professional trajectories. Discussion. The analytical lines make explicit domains operating at structural, disciplinary, hegemonic, interpersonal, and intrapersonal levels. The latter, in particular, reveals tactics that attempt to challenge and reverse inequality through everyday practices. Conclusion and recommendations. The findings derived from the theses provide urgent insights for improving teacher education within an Indigenous education subsystem that remains precarious and reproduces inequality.